The jilted countess : a novel - Ellsworth, Loretta (HarperPerennial, 2026)
"In the aftermath of World War II, a young Hungarian émigré jilted by a G.I. persuades a Midwestern newspaper editor to help her find an American husband in this poignant novel, based on a true story, from the author of The French Winemaker's Daughter. The war stole Roza Meszaros's dreams of becoming a ballerina and her aristocratic family's fortune. But the penniless Hungarian countess's fate takes a hopeful turn when she meets an American soldier named Joe, who promises to marry her and take her to the States. After two years of waiting to obtain the necessary money and paperwork to emigrate, Roza finally arrives in Minnesota-and discovers Joe has married someone else. Determined to stay in America, Roza turns to popular newspaper columnist Cedric Adams to help her find a suitable husband. Sharing Roza's story and her picture, Adams makes a special plea to his military readers. The response is overwhelming-nearly 1,800 World War II veterans bombard the paper's offices with telegrams, flowers, candy, and cash, "a world-record" for marriage proposals, Adams tells Roza. Like a 1948 version of The Bachelorette, Roza ultimately chooses Finn Erickson, a former soldier and railroad locomotive engineer. Putting aside her romantic ideals, she and her new husband settle into the small riverside town of Red Wing, Minnesota. But when Roza unexpectedly runs into her former fiancé, things quickly become complicated. A captivating and unusual tale of love, loss, finding yourself, and creating your destiny, The Jilted Countess examines the meaning of marriage, the American dream, and what it takes to face our demons while searching for happiness"-- Provided by publisher.